1995
DOI: 10.1073/pnas.92.9.3869
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage T7 helicase/primase proteins form rings around single-stranded DNA that suggest a general structure for hexameric helicases.

Abstract: Most helicases studied to date have been characterized as oligomeric, but the relation between their structure and function has not been understood. The bacteriophage T7 gene 4 helicase/primase proteins act in T7 DNA replication. We have used electron microscopy, threedimensional reconstruction, and protein crosslinking to demonstrate that both proteins form hexameric rings around single-stranded DNA. Each subunit has two lobes, so the hexamer appears to be two-tiered, with a small ring stacked on a large ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
210
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(223 citation statements)
references
References 30 publications
13
210
0
Order By: Relevance
“…Most, perhaps all, hexameric helicases operate by this model based upon their ability to pass over a bulky substituent when it is present upon one strand but not the other. Bacteriophage T7gp4B was shown by EM to form hexameric ring structures on M13 DNA [11] and to cleanly unwind with 5 0 to 3 0 polarity if a bulky substrate was placed on the 5 0 strand [28]. For strand displacement assays that incorporate a labeled single-stranded oligonucleotide annealed to M13 DNA, the closed circular M13 DNA itself constitutes the bulky substituent.…”
Section: Helicase Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most, perhaps all, hexameric helicases operate by this model based upon their ability to pass over a bulky substituent when it is present upon one strand but not the other. Bacteriophage T7gp4B was shown by EM to form hexameric ring structures on M13 DNA [11] and to cleanly unwind with 5 0 to 3 0 polarity if a bulky substrate was placed on the 5 0 strand [28]. For strand displacement assays that incorporate a labeled single-stranded oligonucleotide annealed to M13 DNA, the closed circular M13 DNA itself constitutes the bulky substituent.…”
Section: Helicase Operationmentioning
confidence: 99%
“…Superfamily 1 (SF1) and superfamily 2 (SF2) helicases are very prevalent, generally monomeric, and participate in several diverse DNA and RNA manipulations. The other helicase superfamilies form hexameric rings (reviewed in [4]), as demonstrated by biochemistry [5][6][7][8] and electron microscopy studies [9][10][11][12][13][14][15][16][17], and often participate at the replication fork. All of these helicases bind and hydrolyze NTP at the interface between two recA-like domains.…”
Section: Introductionmentioning
confidence: 99%
“…8. For the leading strand replication gel experiments, the initial replication fork consisted of a trunk of a 298 bp dsDNA containing the 601 nucleosome-positioning element, a 30-nucleotide flap of ssDNA to facilitate T7 helicase loading to the replication fork 29,31,56 , and a 1,189 bp dsDNA leading strand.…”
Section: Methodsmentioning
confidence: 99%
“…Electron microscopy and x-ray crystallography illustrated that the protein forms a closed ring-shaped oligomeric structure composed of six or seven subunits (4)(5)(6)(7). Biochemical studies have identified regions critical to oligomerization of the protein, including a linker region that connects the C-terminal helicase domain of the protein to the N-terminal primase domain (8,9).…”
mentioning
confidence: 99%